PENGARUH PENDIDIKAN KEWIRAUSAHAAN DAN MOTIVASI USAHA TERHADAP MINAT BERWIRAUSAHA MAHASISWA SEMESTER VIII UNIVERSITAS BHINNEKA PGRI TAHUN AKADEMIK 2024/2025 - Diana Ayu Kristiana; Sulastri Rini Rindrayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the influence of entrepreneurship education and business motivation on entrepreneurial interest. The subjects of the study were semester VIII students of Bhinneka PGRI University in the 2024/2025 academic year who had taken Entrepreneurship 1 and 2 courses. The study used an associative quantitative approach. Data were collected through questionnaires. The analysis was carried out using multiple linear regression with the help of IBM SPPS Statistics 27 software. The results showed that simultaneously, entrepreneurship education and business motivation had a significant effect on entrepreneurial interest. Partially, entrepreneurship education also had a significant effect on entrepreneurial interest.